Accionar de Enfermerìa en la atención del parto culturalmente adecuado. abril-agosto 2018. - Fray Peñafiel, Evelyn Tatiana (2018)
The proceeding of Nursing in culturally appropriate childbirth care requires special consideration for women since at this stage, it goes through a series of changes, both biological and emotional or social; the mother enters in a process of adaptation where cultural influences, family support, the intervention of the health team play a very important role in the evolution of this process. The aim of this bibliographic review is to systematize the action of Nursing in culturally appropriate childbirth was made in MEDLINE, PUBMED, NURE, MIDWIFERY and REDALYC databases obtaining 61 bibliographical references. The results of review show the criteria of 35 authors who describe the action of Nursing in relation to 10 specific cultural characteristics during cultural birth.